Analysis CPO Production Quality In The Palm Oil Indusry Using Lean Six Sigma Method - Adlul fadillah; Nazaruddin Nazaruddin; Anwardi Anwardi; Muhammad Isnaini Hadiyul Umam; Suherman Suherman (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Within the Crude Palm Oil (CPO) sector, product quality is regarded as a pivotal determinant upon which commercial sustainability rests. PT AAA, an enterprise operating across the estate and manufacturing domains, is engaged in the fabrication of Crude Palm Oil (CPO) alongside Palm Kernel, whereby Fresh Fruit Bunches (FFB) harvested from the oil palm serve as the principal feedstock. Although a sound quality-assurance mechanism has been instituted throughout the manufacturing sequence by the firm, deviations of an unwelcome nature are nonetheless still encountered. The intent pursued by this inquiry is threefold: to pinpoint the imperfections arising in crude palm oil (CPO) output, to dissect the determinants precipitating the deterioration of CPO quality, and to advance remedial proposals grounded in the Lean Six Sigma paradigm. Whereas the tempo and duration of production, or the production sequence as it unfolds, may be scrutinised through Lean, the origins of product imperfection are, by contrast, examined and ameliorated by means of Six Sigma. It is disclosed by the computational outcomes that the imperfections besetting CPO are attributable to a moisture fraction amounting to 66.6% together with an FFA fraction of 33.4%. The output records subjected to examination span a single month, namely January 2023. It should be noted that only the determinants underlying CPO imperfection at PT AAA were appraised in the present work, no corrective measures having been enacted. Keywords: Crude Palm Oil, Free Fatty Acids Level, Lean Six Sigma, Water Content.